TREATMENT OF NATURALLY ACQUIRED STRONGYLOIDES STERCORALIS INFECTION IN A DOG WITH IVERMECTIN - M. Yang; E. B. Gebeyehu; S. J. Jung; O. D. Kwon; D. Kwak (Journal of Animal and Plant Sciences, 2013)
A six month old male Pomeranian weighing 1.1 kg was presented to a local animal clinic with symptoms of diarrohea, depression and emaciation. Faecal examinations, including direct smear and Baermann method, revealed that the dog was severely infected by a parasitic nematode, Strongyloides stercoralis, with a count of 1,200 larvae per gram of faeces. After confirmation, ivermectin (0.05 cc, 1% w/v) was administered subcutaneously. On the second visit after nine days of the first, no larva was detected under microscopy and improvement of body condition was observed with normal stool consistency and body weight of 1.4 kg. The dog was treated again with the same dose of ivermectin and scheduled for another visit in a week. On the third visit, the dog was negative for larval shedding, with normal stool consistency and a slight increase in body weight to 1.8 kg. The dog was scheduled for a final visit in two months to check re-infection; during this visit there were no parasite eggs or larvae and the clinical examination also revealed normal body condition and normal stool consistency with body weight of 3.5 kg, which is within normal range. Thus, the result in the present case suggests that ivermectin is suitable for treatment of dogs naturally infected by S. stercoralis.
Keywords: Strongyloides stercoralis; dog; treatment; ivermectin